The ANDEEP Tanaidacea (Crustacea: Peracarida) revisited I: the family Agathotanaidae Lang, with description of four new species - Larsen, Kim; Bird, Graham; Ota, Mayumi (Zootaxa, 2013)
Specimens collected during the ANDEEP I and II expeditions revealed a number of new species of tanaidacean from the family Agathotanaidae. One new species of Metagathotanais (M. furcilla), two of Paragathotanais (P. diunguisus, P. triunguisus) and one of Paranarthrura, (P. coimbrai) are described in this study. Metagathotanais furcilla can be separated from all other species by the incomplete fusion of the pleonites and the presence of dorsodistal spines of the propodi of pereopods 4–6. Paragathotanais diunguisus can be separated from all other species by the pereopod propodi with numerous distal spines and the numbers of spiniform setae on the pereopod 4–6 dactylus. Paragathotanais triunguisus can be separated from all other species by the numbers of spiniform setae on the pereopod 4–6 dactyli and the lack of maxilliped endite setae. Paranarthrura coimbrai can be separated from most other species on the spines on the propodi and ungues of pereopods 4–6. A key is given to the agathotanaids in the Antarctic/Subantarctic sector. This brings the number of agathotanaid species recorded from the Subantarctic and Antarctic sectors of theAtlantic to nine.